Structural controls of gold mineralisation in Seguelen pit of Siguiri gold mine, Guinea - Beavogui, Massa (Rhodes University, Faculty of Science, Department of Geology, 2015)
The present study provides the results of detailed mapping and analysis of structures encountered in Seguelen pit of Siguiri gold mine, Guinea, where the Siguiri mine is geo-tectonically located in the Baoulé-Mossi domain of Man Shield in West African craton. The gold deposit is hosted in low-grade metamorphic sediments of turbidites sequences which form part of the Lower Proterozoic of Birimian Super group. Three rock formations of Balato, Fatoya and Kintinian underlay the overall pits. The Siguiri gold mine is characterized by the deep weathering profile, developed over the rocks reaching 200 m below the surface in some areas and often capped by the lateritic gravel or duricrust. The rock formations at Seguelen area are characterised by strong bedding monotonously dipping towards SW and trending NW-SE. The lithology of the host rocks has strong control on the disseminated mineralisation throughout the deposit. Two domains of rock formations are clearly distinguished at Seguelen: ï‚§ Fatoya Formation(Ffm) domain ; and ï‚§ Kintinian Formation (Kfm) domain. The two domains are separated by a contact zone of 1.7 m wide parallel to bedding and characterised by the presence of quartz fragments as well as thinly sheeted shale and black shale. This contact zone is identified as disconformity. The major tectonic deformation which has affected the region is known as D2 corresponding to the Eburnean orogeny. The major D2 related structures is the regional thrust striking N-S over an area of 12 km long and 3 km wide and within which corridors all Siguiri gold Mine open pits are located. In the N-S trending structures, there is east-northeast shortening and north-northwest extension. There is pervasive hydrothermal alteration (carbonatization and sideritization) and supergene alteration in the all pits. The hydrothermal alteration attests the intensity of hydrothermal fluid-flow over the host rocks. The hydrothermal fluids flowed along the fractures and within the wall rocks through bedding plans to form numerous auriferous quartz veins bearing disseminated sulphides through chemical reaction between fluids and wall rocks, which are remarkable at Seguelen pit. Three quartz vein sets are distinguished at Seguelen: ï‚§ NNE-SSW quartz vein set ï‚§ NE-SW quartz vein set ï‚§ NW-SE quartz vein set The NE-SW and NNE-SSW quartz veins are often lenticular and associated with the bulk mineralisation.
Keywords: AngloGold Ashanti Ltd.; Gold mines and mining -- Guinea -- Siguiri (Region); Geochemical surveys -- Guinea -- Siguiri (Region); Geology, Structural -- Guinea -- Siguiri (Region); Faults (Geology) -- Guinea -- Siguiri (Region); Folds (Geology) -- Guinea -- Siguiri (Region); Turbidites -- Guinea -- Siguiri (Region); Metamorphism (Geology) -- Guinea -- Siguiri (Region); Hydrothermal alteration -- Guinea -- Siguiri (Region)